2016
DOI: 10.3390/ma9100814
|View full text |Cite
|
Sign up to set email alerts
|

A Numerical Investigation of the Thermal Stresses of a Planar Solid Oxide Fuel Cell

Abstract: A typical operating temperature of a solid oxide fuel cell (SOFC) is quite high above 750 °C and affects the thermomechanical behavior of the cell. Thermal stresses may cause microstructural instability and sub-critical cracking. Therefore, a joint analysis by the computational fluid dynamics (CFD) and computational structural mechanics based on the finite element method (FEM) was carried out to analyze thermal stresses in a planar SOFC and to predict potential failure locations in the cell. A full numerical m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 15 publications
1
20
0
Order By: Relevance
“…During the last two decades, the attention to SOFC has been drawn and the number of the experimental and numerical research papers has been increased considerably. [4][5][6][7][8][9][10] Unfortunately, the high-temperature operation of SOFCs has several drawbacks such as limited material selection, accelerated morphological and chemical degradation, and enhanced diffusion of components and impurities between adjacent layers and on the surface. Most researchers nowadays focus on the thermal stress inside the SOFC, [11][12][13][14] They studied the delamination and degradation of SOFCs electrode/electrolyte estimated by calculating the stresses generated within the different layers of the cell.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the last two decades, the attention to SOFC has been drawn and the number of the experimental and numerical research papers has been increased considerably. [4][5][6][7][8][9][10] Unfortunately, the high-temperature operation of SOFCs has several drawbacks such as limited material selection, accelerated morphological and chemical degradation, and enhanced diffusion of components and impurities between adjacent layers and on the surface. Most researchers nowadays focus on the thermal stress inside the SOFC, [11][12][13][14] They studied the delamination and degradation of SOFCs electrode/electrolyte estimated by calculating the stresses generated within the different layers of the cell.…”
Section: Introductionmentioning
confidence: 99%
“…However, this technology still faces many challenges such as cost reduction and an extended lifetime operation. During the last two decades, the attention to SOFC has been drawn and the number of the experimental and numerical research papers has been increased considerably 4‐10 . Unfortunately, the high‐temperature operation of SOFCs has several drawbacks such as limited material selection, accelerated morphological and chemical degradation, and enhanced diffusion of components and impurities between adjacent layers and on the surface.…”
Section: Introductionmentioning
confidence: 99%
“…While fuel cell degradation is mainly attributed to the materials and catalyst physicochemical properties and fuel contaminations, 2,3 it is also strongly linked to the thermal instability and stress. 4,5 The latter is particularly important in SOFC case operating at elevated temperatures (700-900 o C) with a high temperature gradients across stack dimensions.…”
Section: Introductionmentioning
confidence: 99%
“…and Pianko‐Oprych et al. also made an extensive study on planar SOFC stack involving computational fluid dynamics together with structural mechanics shedding light on the transient thermal behavior of the stack and the correlation between stress and operational voltage in the SOFC .…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Greco et al showed that the probability of failure of the cells in an operating stack decreases over time due to relaxation of stresses, and the probability of failure peaks at the shifts between operation point [7]. Peksen et al and Pianko-Oprych et al also made an extensive study on planar SOFC stack involving computational fluid dynamics together with structural mechanics shedding light on the transient thermal behavior of the stack [4] and the correlation between stress and operational voltage in the SOFC [14].…”
Section: Introductionmentioning
confidence: 99%